Efeitos de diferentes treinamentos com pequenos jogos de basquetebol sobre os desempenhos físico e tático-técnico de jovens atletas - Sarah da Glória Teles Bredt (2022)
The small-sided games (SSG) are a means of training of team sports and present some characteristics similar to the formal game. Coaches and physical trainers can change SSG characteristics to demand different responses from athletes (physical, physiological, and tactical-technical). In addition, previous studies have shown that the use of SSG training can improve athletes’ physical performance. However, these studies did not compare the effect of different types of SSG training on athletes’ physical performance nor tactical-technical performance during the formal game. These data are important to support the SSG as a means of training and to help coaches to better choose the SSG during the training process. Therefore, this study aimed to 1) compare the effects of two basketball SSG trainings (SSG performed on full court with two hoops and SSG performed on half court with one hoop) on athletes’ physical performance and 2) compare the effect of two SSG trainings on tactical-technical performance during the formal game (5vs.5 with official rules). Two squads from different clubs participated in the study (squad 1, U-15, 21 athletes; squad 2, U-14, 22 athletes). Athletes from each squad were divided into three groups: two experimental (Full-court Group – FCG and Half-court Group – HCG) and one control (CONG). These groups performed the training protocols twice a week over an 8-week period (30-40-minute sessions). The research training interventions comprised 3vs.3 small-sided games in full court with two hoops (FULL), 3vs.3 in half court with one hoop (HALF), and a technical-physical circuit training (CON). Groups were tested at the beginning, after four weeks and after eight weeks of the research training intervention for aerobic performance (Yoyo Intermittent Recovery Test level 1), vertical jump performance (countermovement jump), change of direction performance (T test), and sprint performance (5, 10, and 20 meters sprints). Athletes also participated in formal games at the beginning and at the end of the research training intervention (eight weeks) to evaluate its impact on athletes’ tactical-technical performance. The tactical-technical performance was assessed using the Space Creation Dynamics applied to the different types of offense (set offenses and fast-breaks) and according to actions’ performance (actions that resulted in a scored shot or free/facilitated shot by the defender). Mixed ANOVAs with two factors were used to compare the physical performance between the factor “type of SSG training”, with three levels (FULL, HALF, and CON) and the factor “time” with two (pre and after four weeks) or three levels (pre, after four, and after eight weeks). ANOVAS-type statistics were used to compare the medians of the tactical-technical variables between assessments pre and after eight weeks of training. In all cases, statistical significance was set at 5%. For the physical performance, results showed that all training groups significantly increased performance in all tests, except for the time spent to change Direction to the right side. For tha tactical-technical performance, there was a main effect of time, with similar significant increases for all groups, related to the space creation without the ball during the fast-breaks and post isolations during the set offenses. There was a significant interaction for the number of offenses with no shot, with lower values (higher performance) for the FULL group in the assessment after eight weeks of training compared to the other groups, indicating that the FULL group presented a lower frequency of rule violations and mistakes that resulted in the loss of ball for the other team before shooting to the basket. Finally, there was a non-expected effect for the performance of on-ball screen and space creation with ball dribbled, with lower values for the CON group. We concluded that four weeks of basketball SSG training (two sessions per week, with three-to-five 4-minute bouts) on full and half court similarly increase the physical performance of young basketball 11 athletes during the preseason; this increase is similar to that induced by a circuit training with and without the ball on the aerobic, sprints’, jump’s and change of direction’s performance. Eight weeks of SSGs training planned to develop physical conditioning (two sessions per week, with three-to-five 4-minute bouts) and with an implicit learning focus do not contribute to increase tactical-technical performance of group actions during the formal game. Although the physical and tactical-technical demands of SSGs performed on full and half court are different, it seems that longer training periods with these SSGs are needed to promote distinct adaptations in basketball athletes.